Design and development of a cable actuation unit - Kwek, Qing Wei. (2010)
A Cable-driven manipulator system has the potential to perform tasks that could not be performed by a conventional robot system. In a cable-driven system, the rigid links of the normal manipulator are being replaced by cables, thus reducing the inertia of the system. This allows the cable-driven system to possess high load capacity, high speed and large workspace simultaneously. However, there is redundancy in actuation as the number of actuators needed is more than the degrees of freedom. This is due to the unilateral property of cables. All Cabledriven Systems require an actuation unit to control the each cable for coordinated motion of the end effector. Therefore, the design of an actuation unit with good performance characteristic is important in order to achieve control of the end effector. This report concerns the design of a cable actuation unit that will meet to the proposed design requirements and parameters. The emphasis of the design is placed on accuracy, simplicity and cost, aiming to achieve one that is easy to manufacture and maintain. From the conceptual stage to embodiment and detail design stage, each part of the design is examined closely to refine the preliminary layout. The objective is to produce a more compact and efficient design that will cater to the functionality of each individual part. In addition, tests are also conducted on different cables to obtain a better understanding of the characteristics and aid in the selection. The design is fabricated and tested with the selected cable for accuracy, repeatability and performance. The experimental results show that the prototype is able to meet the design requirement. In particular, it is able to pull a load of 100N at a speed of 0.10 m/s over a distance of 0.15m. Furthermore, the total cost to produce one prototype exclusive of the motor is kept below $400. This means that the prototype is feasible for system that requires many actuation units and is capable of accurate and precise results. The balance between cost and performance will enhance the potential of cable manipulator systems in many applications.